The Broadband Futures Forum: Regional and Rural Broadband Access: City standards in 10 years? - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2021)
On 24 March 2021, TelSoc hosted the sixth Broadband Futures Forum, held online, with a focus on regional and rural broadband access. Mr Gavin Williams from NBN Co, the developer of Australia’s National Broadband Network (NBN), spoke about developments in Fixed Wireless and Satellite services and described NBN Co’s commitment to ongoing enhancement of broadband access in regional and rural Australia. A question-and-answer session followed the presentation in which Mr Williams fielded a variety of questions on broadband access and technological developments.